2014
DOI: 10.1103/physreve.89.032811
|View full text |Cite
|
Sign up to set email alerts
|

Topological implications of negative curvature for biological and social networks

Abstract: Network measures that reflect the most salient properties of complex large-scale networks are in high demand in the network research community. In this paper we adapt a combinatorial measure of negative curvature (also called hyperbolicity) to parametrized finite networks, and show that a variety of biological and social networks are hyperbolic. This hyperbolicity property has strong implications on the higher-order connectivity and other topological properties of these networks. Specifically, we derive and pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
81
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 45 publications
3
81
0
Order By: Relevance
“…This confirms the results in [4]. However, unlike previous efforts, we analyze the relationship between the hyperbolicity and other global parameters of the graph.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…This confirms the results in [4]. However, unlike previous efforts, we analyze the relationship between the hyperbolicity and other global parameters of the graph.…”
Section: Introductionsupporting
confidence: 89%
“…Multiple complex networks such as the Internet [28,14], data networks at the IP layer [24], and social and biological networks [4,2] show low δ-hyperbolicity (low hyperbolicity suggests a structure that is close to a tree structure [14,3]). Also, it has been observed that networks with this property have highly connected cores [24].…”
Section: Introductionmentioning
confidence: 99%
“…This forces the sides of the triangle to be curved toward its center as its size increases. 7 Multiple complex networks such as the Internet, 8,9 data networks at the IP layer, 6 and social and biological networks 10,11 show low -hyperbolicity (low hyperbolicity suggests a structure that is close to a tree structure 12 ). Also, it has been observed that networks with this property have highly connected cores.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the notion of δ-hyperbolicity [22] has been generalized and studied in different types of networks [23][24][25][26][27][28]. It has been shown that the occurrence of negative curvature has implications on the navigability and dynamic processes in networks [29,30]. The issue of precise mechanisms is still open, perhaps depending on the type of dynamics.…”
Section: Introductionmentioning
confidence: 99%